Cold Plasma Characteristics and Applications in Medicine (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Non-equilibrium plasma (or low-temperature plasma, LTP) offers a chemically rich medium without the need for high power and elevated temperatures. This unique characteristic has made LTP very useful for various industrial and biomedical applications where thermal effects are not desirable. In addition, the relative simplicity of the design of sources capable of generating non-equilibrium plasma at atmospheric pressure makes LTP a very attractive technology that can accomplish the same or better results than much more complex and expensive approaches. This book describes various low-temperature plasma sources and some of their environmental and biomedical applications. The plasma sources covered in this book include low-temperature plasma jets which are novel devices that can launch low-power, low-temperature plasma plumes in ambient air. These plasma plumes can accurately and reliably be aimed at a surface to be treated or at a biological target such as cells and tissues. The application of these plasma jets in medicine, including in cancer therapy, are thoroughly discussed in this book. The contents of this book will appeal to engineers, medical experts, academics, and students who work with plasma technology.